Multifunctional role of DEAD-box helicase 41 in innate immunity, hematopoiesis and disease - Ma, Jing; Ross, Susan R. (Frontiers in Immunology, 2024)
DEAD-box helicases are multifunctional proteins participating in many aspects of cellular RNA metabolism. DEAD-box helicase 41 (DDX41) in particular has pivotal roles in innate immune sensing and hematopoietic homeostasis. DDX41 recognizes foreign or self-nucleic acids generated during microbial infection, thereby initiating anti-pathogen responses. DDX41 also binds to RNA (R)-loops, structures consisting of DNA/RNA hybrids and a displaced strand of DNA that occur during transcription, thereby maintaining genome stability by preventing their accumulation. DDX41 deficiency leads to increased R-loop levels, resulting in inflammatory responses that likely influence hematopoietic stem and progenitor cell production and development. Beyond nucleic acid binding, DDX41 associates with proteins involved in RNA splicing as well as cellular proteins involved in innate immunity. DDX41 is also a tumor suppressor in familial and sporadic myelodysplastic syndrome/acute myelogenous leukemia (MDS/AML). In the present review, we summarize the functions of DDX helicases in critical biological processes, particularly focusing on DDX41's association with cellular molecules and the mechanisms underlying its roles in innate immunity, hematopoiesis and the development of myeloid malignancies.